2018
DOI: 10.1021/acscentsci.8b00139
|View full text |Cite
|
Sign up to set email alerts
|

Slow Dynamics around a Protein and Its Coupling to Solvent

Abstract: Solvent is essential for protein dynamics and function, but its role in regulating the dynamics remains debated. Here, we employ saturation transfer electron spin resonance (ST-ESR) to explore the issue and characterize the dynamics on a longer (from μs to s) time scale than has been extensively studied. We first demonstrate the reliability of ST-ESR by showing that the dynamical changeovers revealed in the spectra agree to liquid–liquid transition (LLT) in the state diagram of the glycerol/water system. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(99 reference statements)
1
15
0
Order By: Relevance
“…To prepare cleaved Bid (cBid) and T4 lysozyme (T4L), we followed the protocols that we previously published 36 , 37 .…”
Section: Methodsmentioning
confidence: 99%
“…To prepare cleaved Bid (cBid) and T4 lysozyme (T4L), we followed the protocols that we previously published 36 , 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Change in the dynamics of bulk solvent with temperature was obtained by studying the ST‐ESR spectra of TEMPOL free probe (Figure B). ST‐ESR was shown, for the first time, to have sufficient sensitivity to the dynamical changes upon crossing over LLT in the water/glycerol phase diagram . Because of the sufficient sensitivity to slow dynamics in the temperature range (180–240 K), the study showed that although LLT of solvent changes with solvent composition (at varying glycerol/water mixtures), protein retains a dynamical changeover around 220 K. It revealed that protein and water dynamics are not necessarily coupled as what was thought.…”
Section: Sensitivity Enhancement In Esr For Protein/water Interactionsmentioning
confidence: 99%
“…With the introduction of three different spin labels to same individual sites in T4L protein ( Figure 5C), the recents tudys ystematically mapped out the variation in local (site-specific) dynamics around ap rotein surface( at 180-240K)i nafully hydrated state. [96] Temperature-dependentd ynamics of protein was studied by the ST-ESR spectrao fR 1s ide chain (with a chain length of 6-7 ), followed by ar eplacement of R1 by K1 (with ac hain length of 12-13 )t oi ncreaset he contribution of bulk solventt ot he spectra, and by RX (with ac hain length of 5-6 )toi ncrease the weight of protein backbone dynamics in the spectra ( Figure 5D). (Note that RX is featured by its highly restricted internal motion and thus has proven useful for monitoring motion of the protein backbone to which it is attached without complications arising from internal modes of the side chain.…”
Section: Saturation Transfer Esr Reveals the Slow Dynamics Aroundapromentioning
confidence: 99%
“…Indeed, detailed calculations based in T-matrix theory have recently confirmed that, at low temperature, polaron energy does decrease with increasing temperature [25]. Proteins have also been shown to exhibit dynamics that are strongly coupled to the surrounding solvent [20], and they have been observed to migrate from cold to hot at low enough temperatures [5,11], suggesting that their energy is a non-monotonic function of the temperature. More recently, lipid vesicles have been shown to also exhibit thermophilic motion over a wide range of ambient temperatures [12].…”
mentioning
confidence: 99%
“…2.3] for a recent survey), to our knowledge no single satisfactory mechanism has been proposed to account for this phenomenon. However, it has recently been shown by means of saturation transfer electron spin resonance that the low temperature dynamics of proteins are strongly coupled to the dynamics of the surrounding solvent [20]. This suggests strong coupling as the reason behind anomalous low-temperature motion, as is the case of negative thermophoresis.…”
mentioning
confidence: 99%